Separation of drying strains and the calculation of drying stresses considering the viscoelasticity of red pine wood during drying. Issue 15 (18th November 2017) - Han, Yeonjung; Yang, Sang-Yun; Park, Jun-Ho; Chang, Yoon-Seong; Eom, Chang-Deuk; Yeo, Hwanmyeong
ABSTRACT: The objective of this study was to separate drying strains into elastic, viscoelastic, and viscous strains using free shrinkage and recovery from the deformation of slices at stress relief. The apparent shrinkage deformation was obtained by measuring the change in width of drying specimens during drying. Using the slice method, elastic and viscoelastic deformation were defined as the instantaneous change in width of a slice right after cutting and the change in the width of a slice with constant moisture content during 48 h, respectively. Viscous deformation, permanent and nonrecoverable deformation of wood, was defined as the difference in deformation between free shrinkage and the sum of the apparent, elastic, and viscoelastic deformations. These elastic, viscoelastic, and viscous strains were applied to a viscoelastic model, and coefficients of viscoelasticity and viscosity were derived. The drying stress and deformation of red pine wood at specific times during the drying process can be predicted using each coefficients and modulus of elasticity obtained by experiment.